MEWARNAI SAMBIL BELAJAR: UPAYA EDUKASI RABIES PADA ANAK SEKOLAH DASAR DI DESA NUNHILA, TIMOR TENGAH SELATAN - Ndaong, Nemay Anggadewi; Laut, Meity Marviana; Nitbani, Heny; Amalo, Filphin Adolphin; Selan, Yulfia Nelymalik; Maha, Inggrid Trinidad; Saputra, Agus (Jurnal Media Tropika, 2025)
Rabies remains a critical public health concern, particularly in areas with limited resources and insufficient preventive efforts. Early education plays a vital role in raising awareness and promoting preventive behavior. This community service activity aimed to educate elementary school children about rabies through a creative and enjoyable method—coloring activities. The program was conducted at SD Inpres Nenonaheun, located in Nunhila Village, Mollo Barat Sub-district, Timor Tengah Selatan Regency, East Nusa Tenggara, Indonesia. It involved interactive coloring sessions using rabies-themed educational materials specifically designed for children aged 7 to 12. This activity combined visual learning and storytelling to convey essential information about rabies transmission, symptoms, and prevention. Evaluation through pre- and post-activity questionnaires revealed a significant improvement in the children's understanding of rabies. The use of coloring activities as an educational tool proved to be an effective strategy for raising awareness among elementary school students, indicating its potential for broader application in similar rural settings.